Հայ ժողովրդի մեծ ողբերգությունը - Մ. Գ. Ներսիսյան (ՀՀ ԳԱԱ հրատ.)
Геноцид армян 1915—1916 гг.-одна из самых черных страниц историй человечества. Пантюркистское правительство младотурок по заранее продуманной и запланированной программе в течение двух лет уничтожило до полутора миллиона армян,был осуществлен первый геноцид XX века. Об этом страшном преступлении турецкого правительства создана обширная литература, об этом писали не только армяне, но и многие иностранные ученые, писатели и официальные лица. Факт геноцида всесторонне был доказан также во время судебных процессов, проведенных в Константинополе (1919 г.), Берлине (1921г.), Париже (1984 г.). The 1915—1916 genocide of the Armenians is one of the dark pages of the history of mankind. Pan-Turkish government of the young-Turcs exterminated about 1,5 million Armenians by a premeditated and planned program within two years. The first genocide of the XX century was committed. There is a voluminous literature about that terrible crime of the Turkish government. Many Armenians, as well as foreign scientists, writers and officials wrote about it. The fact of the genocide was thoroughly proved also in the trials in Constantinopole (1919), in Berlin (1921), in Paris (1984).
Keywords: History; Armenian Genocide (1915); D History